Oxygen Permeation Resistances and Routes in Nanoscale Ionomer Thin Film on Platinum Surface. Issue 1 (29th January 2021) - Fan, Linhao; Wang, Yun; Jiao, Kui
Abstract : Understanding the O2 permeation resistance and its dependence on the material structure in an ionomer thin film on a platinum surface is vital for the electrocatalyst performance at low platinum loading in proton exchange membrane fuel cells. In this study, the ionomer film nanostructure and O2 permeation resistances and routes at different water contents are investigated using molecular dynamics (MD) simulations. The MD model is reasonably validated, and simulation results show that the ionomer film contains three regions according to their structures. The dense layer with a tight arrangement of perfluorosulfonic acid (PFSA) chains in the ionomer-Pt interface (Region I) has a density ∼1.5–2 times higher than that in the bulk-like ionomer (Region II). The overall O2 permeation resistance increases with decreasing water content and the ionomer-Pt interface plays a dominant role in the O2 resistance due to its high-density structure. The study on O2 permeation routes shows that O2 mainly permeates via the water sites in the ionomer-Pt interface and thus a lower resistance is present at higher water contents. In the bulk-like ionomer, O2 mainly permeates via small cavities at low water contents and the large interfacial areas between water clusters and PFSA frameworks at high water contents.